Organometallic‐Mediated Radical Polymerization of Vinylidene Fluoride. (16th February 2018) - Banerjee, Sanjib; Ladmiral, Vincent; Debuigne, Antoine; Detrembleur, Christophe; Poli, Rinaldo; Améduri, Bruno
Abstract: An unprecedented level of control for the radical polymerization of vinylidene fluoride (VDF), yielding well‐defined PVDF (at least up to 14 500 g mol −1 ) with low dispersity (≤1.32), was achieved using organometallic‐mediated radical polymerization (OMRP) with an organocobalt compound as initiator. The high chain‐end fidelity was demonstrated by the synthesis of PVDF‐ and PVAc‐containing di‐and triblock copolymers. DFT calculations rationalize the efficient reactivation of both head and tail chain end dormant species.